Selection and appointment of judges in the Republic of Kazakhstan: development of legislation and problematic aspects in the formation and activities of the Supreme Judicial Council of the Republic of Kazakhstan - Abdrasulov Е.Б.; Saktaganova А.Б.; Zhenissov С.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
Based on the analysis of the development of legislation and the identification of gaps and shortcomings in it, this paper suggests ways to improve the system of selection and appointment of judges in the Republic of Kazakhstan, which is of great importance for the independent functioning of the judiciary and the implementation of the rule of law. In world practice, there are many ways to develop an effective and professional judicial corps. It is not necessary that all the mechanisms known from the legislation and experience of many countries are involved in this process. The authors believe that the fact of borrowing a certain mechanism, even tested in the activities of individual countries, cannot guarantee its efficiency in Kazakhstan. Indeed, various forms such as legislative prescriptions play an important role in this process, but no less important is the correct implementation of democratic world trends in the established legislative provisions, filling formal requirements with clear and legitimate content, which is ensured by the correct legal policy of the state, high-quality legal technology of legislation and the appropriate application of legal standards.